Efficacy of macrocyclic lactones against gastrointestinal nematodes of bovines and their effect on eggs in the uterus of females of these parasites - Zapa, Dina María Beltrán; Maciel, Willian Giquelin [UNESP]; Teixeira, Weslen Fabricio Pires; Felippelli, Gustavo [UNESP]; Gomes, Lucas Vinicius Costa [UNESP]; Ferreira, Lorena Lopes; Amarante, Alessandro Francisco Talamini [UNESP]; da Costa, Alvimar José [UNESP]; Borges, Fernando de Almeida; Soares, Vando Edésio; Lopes, Welber Daniel Zanetti (Elsevier, 2025)
This study evaluated the effect of the injectable macrocyclic lactones (ML) ivermectin (IVE), abamectin (ABA), eprinomectin (EPR), doramectin (DOR) and moxidectin (MOX) on the number of eggs present in the uterus of strongyles from naturally infected cattle. In addition, the efficacy and diagnosis of resistance were assessed. Animals were treated (n = 8 for each ML) on day 0 of the study and necropsied on D+ 14. The number of eggs present in the uterus of the females and the lengths of Haemonchus placei, Oesophagostomum radiatum, Trichostrongylus axei and Cooperia spp. were measured. In addition, fecal egg counts (FEC) were performed, and the results showed efficacies for IVE, ABA, EPR, DOR and MOX, respectively, of 88.9 %, 76.9 %, 58.2 %, 62.3 % and 92.5 %. Through CET, H. placei and C. punctata populations were diagnosed as resistant to all ML tested except MOX. The populations of C. pectinata were resistant to ABA, EPR and DOR, while results were inconclusive for IVE and MOX. T. axei was resistant to IVM, while O. radiatum was resistant to all ML except IVM. In general, all ML significantly (p < 0.05) reduced the mean number of eggs in the uterus of females collected from treated animals (ranging from 11.1 % for IVER/O. radiatum to 94.2 % for MOX/T. axei), except MOX for O. radiatum. The mean length of the females collected from treated animals was shorter (p < 0.05) than in the control group. When the parasite resistance process is incipient for the most common and prolific strongyle species in each population, the clinical diagnosis of resistance through the fecal egg count reduction test (FECRT) showed some inconsistencies compared to the controlled efficacy test (CET).
Keywords: CET; FECRT; Female uterus length; Gastrointestinal nematodes; Macrocyclic lactones; Nematode oviposition